2006
DOI: 10.1095/biolreprod.105.045328
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory Cytokines Found in Amniotic Fluid Induce Collagen Remodeling, Apoptosis, and Biophysical Weakening of Cultured Human Fetal Membranes1

Abstract: The mechanisms by which fetal membranes (FM) rupture during the birth process are unknown. We have recently reported that FM weaken, at least in part, because of a developmental process of extracellular matrix remodeling and apoptosis. We now hypothesize that cytokines that normally increase in amniotic fluid at term induce FM collagen remodeling and apoptosis with concomitant weakening. Full-thickness FM fragments were cultured with (0-100 ng/ml) or without tumor necrosis factor (TNF) or interleukin 1, beta (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
105
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(119 citation statements)
references
References 27 publications
10
105
0
4
Order By: Relevance
“…Thus we conclude that MMP-9 plays a major role in FM remodeling, weakening and rupture. Our work also demonstrates that MMP-9 levels are an excellent marker for FM strength (El-Khwad et al, 2005Kumar et al, 2006; R.M. Moore et al, 2009b) [Fig.…”
Section: Term Fm Develops a Para-cervical "Weak Zone" Where Rupture Isupporting
confidence: 63%
“…Thus we conclude that MMP-9 plays a major role in FM remodeling, weakening and rupture. Our work also demonstrates that MMP-9 levels are an excellent marker for FM strength (El-Khwad et al, 2005Kumar et al, 2006; R.M. Moore et al, 2009b) [Fig.…”
Section: Term Fm Develops a Para-cervical "Weak Zone" Where Rupture Isupporting
confidence: 63%
“…Increased PGE2 production in the amnion could diffuse through the chorion and decidua to stimulate myometrial cell prostaglandin production and hence contractility (Slater et al, 1999, Smith, 2007. The fetus and placenta may also jointly trigger fetal membrane rupture, since prostaglandins, TNF-α and corticotrophin releasing hormone (CRH) (which also rise in the amniotic fluid towards term (Alvi et al, 1999, Laatikainen et al, 1988) all stimulate the production of MMP-9, which weakens the membranes and thus facilitates membrane rupture (Kumar et al, 2006, Young et al, 2002.…”
Section: Fetal Membranesmentioning
confidence: 99%
“…To address these shortcomings, we developed an in vitro explant model system in which human fetal membrane rupture strength, which is the major parameter of clinical interest, and concomitant (and presumably causative) biochemical changes within the fetal membrane can be measured accurately. [8][9][10] Using this system, we found that cytokines such as tumor necrosis factor-a (TNF) and interleukin 1ß, which induce tissue level inflammation, and thrombin, which causes changes that are associated with abruption and bleeding, markedly weaken full-thickness fetal membrane. 4,9,11,12 Concomitant with weakening, these agents induce biochemical and histologic tissue changes that mimic those seen in the physiologic weak zone (fetal membrane rupture initiation site) in the fetal membrane region overlying the cervix.…”
mentioning
confidence: 99%